"Failure to Rescue" as a Novel Quality Metric in Pediatric Liver Transplantation. Issue 4 (April 2016) - Rela, Mohamed; Reddy, Mettu Srinivas
Abstract : The authors provide a deeper perspective on the concept of "failure to rescue" in pediatric liver transplantation. They emphasize the importance of "field strength." That is, the expertise and training of the institutional team beyond the primary transplant clinicians in establishing liver transplantation. This topic is critical as transplantation spreads across the developing international landscape.